PENYULUHAN GIZI SEIMBANG DI MASA PANDEMI COVID-19 PADA SISWA SMA PLUS PGRI CIBINONG - Sabrina Wijaya,; Sugiatmi, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Pandemic Covid-19 has brought about changes in everyday life. One of the things that play a role in tackling exposure to Covid-19 is food selection. Food plays an important role before, during, and after infection. Good nutritional knowledge will affect one's actions in fulfilling nutritional needs through food consumption. The existence of nutritional knowledge can affect a person's intake through the selection of balanced nutritious foods that he consumes in order to achieve optimal nutritional and health status. The higher a person's nutritional knowledge, it is expected that they will pay more attention to their food consumption in terms of quality and type of food choices. The purpose of this study was to determine the level of knowledge before and after being given counseling about balanced nutrition. The partner in this activity is SMA Plus PGRI Cibinong. This activity was carried out online to the culinary arts students of SMA Plus PGRI Cibinong, as many as 31 respondents. The extension method is carried out through webinars by providing education through lectures, discussions, questions and answers, and games. In this activity, pre test and post test forms were also filled through google form. The results showed that from 31 respondents, it was found that before the counseling was carried out, the level of knowledge of students in the good category was 35.5%. Meanwhile, after counseling the percentage of students with good categories increased to 96.8%. So it can be concluded that there was a significant increase in the level of student knowledge after being given counseling about balanced nutrition. It is expected that students will further increase their knowledge and can apply knowledge in choosing the nutritional intake needed every day so that they can maintain their health.